2017
DOI: 10.2147/ndt.s133433
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations and dosing of 2 long-acting injectable formulations of aripiprazole

Abstract: Maintaining therapeutic plasma concentrations of an antipsychotic agent is essential in preventing relapse of symptoms in schizophrenia. Long-acting injectable (LAI) formulations provide extended exposure to antipsychotic therapy and have been useful in addressing treatment nonadherence. Aripiprazole is an atypical antipsychotic used in the treatment of schizophrenia and is available in 2 chemically different (aripiprazole monohydrate and aripiprazole lauroxil [AL]) and pharmaceutically different LAI formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Although the aripiprazole lauroxil 882 mg injection contains aripiprazole 600 mg whereas aripiprazole monohydrate 400 mg contains aripiprazole 400 mg, median steady-state plasma concentrations were similar, raising uncertainty around the dose equivalence data. Thus, plasma concentrations from different formulations may reflect not just the dose administered but the absorption of the drug from the depot aripiprazole [ 40 ]. However, these data should be interpreted with caution, as the data inputs from different time points and different steady-state concentrations (average vs. minimum) were compared.…”
Section: Second-generation Lai Antipsychoticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the aripiprazole lauroxil 882 mg injection contains aripiprazole 600 mg whereas aripiprazole monohydrate 400 mg contains aripiprazole 400 mg, median steady-state plasma concentrations were similar, raising uncertainty around the dose equivalence data. Thus, plasma concentrations from different formulations may reflect not just the dose administered but the absorption of the drug from the depot aripiprazole [ 40 ]. However, these data should be interpreted with caution, as the data inputs from different time points and different steady-state concentrations (average vs. minimum) were compared.…”
Section: Second-generation Lai Antipsychoticsmentioning
confidence: 99%
“…Dose equivalencies with the oral formulation are shown in Table 3. Salzman et al [40] compared plasma concentrations of aripiprazole between once-monthly dosing of aripiprazole monohydrate 400 mg and aripiprazole lauroxil 882 mg. Although the aripiprazole lauroxil 882 mg injection contains aripiprazole 600 mg whereas aripiprazole monohydrate 400 mg contains aripiprazole 400 mg, median steady-state plasma concentrations were similar, raising uncertainty around the dose equivalence data.…”
Section: Aripiprazole Lauroxilmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors suggest a therapeutic range of 150-210 ng/ml [66]. A study showed that the 2 available LAI formulations of aripiprazole, AM 400 mg and AL (aripiprazole lauroxil) 882 mg administered every 4 weeks, provide similar plasma concentrations of aripiprazole, indicating no correlation between the IM dosage and PLs [67]. In the presented study, patients treated with AM showed a stable clinical condition, as evidenced by clinical evaluation scales time course, despite PLs showing values below the recommended range, generally referred to oral formulations; this could suggest the utility of plasma monitoring in order to identify a lower therapeutic range for the LAI formulation in the light of the more favorable and regular pharmacokinet-ic profile of LAI antipsychotics compared to oral formulations [62,68].…”
Section: Plasma Levelsmentioning
confidence: 99%
“…The recent publication by Salzman et al 1 compared pharmacokinetic (PK) data from population PK (popPK) models for two long-acting antipsychotic formulations: aripiprazole once-monthly 400 mg (AOM 400) and aripiprazole lauroxil (AL). We would like to address a few major concerns.…”
mentioning
confidence: 99%